Performance and health concepts in artistic gymnastics - Bradshaw, E. J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Artistic gymnastics attracts a large number of children and offers a range of participation levels. Gymnastics starts for many with Kinder gym classes which are aimed at the development of fundamental motor skills in a game-like gymnastics environment. Most children will continue onto recreational (non competitive) gymnastics or to a nationally structured competitive program, with a select few then going onto high intensity elite training and competition from as early as 6 to 8 years of age. Considerable variability is evident in the ability of gymnasts to perform each of the apparatus during competition at all levels (interclub, state, national, international) often due to the individual variation in physical attributes. Gymnastics requires explosive sprinting, jumping, pushing and pulling skills, together with balance and artistry on four apparatus for women (beam, uneven bars, floor, vault) and five for men (high bar, parallel bars, pommel horse, floor, vault). In competition these apparatus routines are judged subjectively by a panel of judges to identify the content and difficulty (D score) and the perfection in execution (E score).